Advances in the genetic dissection of plant cell walls: tools and resources available in Miscanthus - Slavov, Gancho; Allison, Gordon G.; Bosch, Maurice (Frontiers in Plant Science, 2013)
Tropical C4 grasses from the genus Miscanthus are believed to have great potential as biomass crops. However, Miscanthus species are essentially undomesticated, and genetic, molecular and bioinformatics tools are in very early stages of development. Furthermore, similar to other crops targeted as lignocellulosic feedstocks, the efficient utilisation of biomass is hampered by our limited knowledge of the structural organisation of the plant cell wall and the underlying genetic components that control this organisation. The Institute of Biological, Environmental and Rural Sciences (IBERS) has assembled an extensive collection of germplasm for several species of Miscanthus. In addition, an integrated, multidisciplinary research programme at IBERS aims to inform accelerated breeding for biomass productivity and composition, while also generating novel fundamental knowledge. Here we review recent advances with respect to the genetic characterisation of the cell wall in Miscanthus. First, we present a summary of recent and on-going biochemical studies, including prospects and limitations for the development of powerful phenotyping approaches. Second, we review current knowledge about genetic variation for cell wall characteristics of Miscanthus and illustrate how phenotypic data, combined with high-density arrays of single nucleotide polymorphisms, are being used in genome-wide association studies to generate testable hypotheses and guide biological discovery. Finally, we provide an overview of the current knowledge about the molecular biology of cell wall biosynthesis in Miscanthus and closely related grasses, discuss the key conceptual and technological bottlenecks, and outline the short-term prospects for progress in this field.